A Analysis of government internal control systems in management of village funds (according to government regulation number 190 of 2021) (case study in cibatok ii village, cibungbulang district, bogor regency) - Fanaisyah, Denissa; Indupurnahayu, Indupurnahayu; Hurriyaturrohman, Hurriyaturrohman (Jurnal Ekonomi, Manajemen dan Akuntansi (JEKMA), 2023)
This study aims to determine the Analysis of the Government's Internal Control System in the Management of Village Funds in Cibatok II Village, Cibungbulang District, Bogor Regency. The research method used in this study is a qualitative approach using descriptive methods where the results of research data are in the form of information collected through observation, interviews and documentation that is reviewed. This research uses primary data obtained directly from the main source. This data collection uses a question and answer process with village officials, namely the Village Head, Village Secretary and Village Treasurer. The data that has been collected will be processed and then analyzed to answer what is in the formulation of this research problem.Based on the analysis that has been carried out in this study, the theory and practice implemented in managing village funds have not fully implemented internal control in managing village funds according to PMK Number 190 of 2021 because there is still an uneven distribution of village funds in the Direct Cash Assistance program to the poor so that The Village Government must further improve the performance or data collection of its residents. Keywords: village funds. government internal control system, management of village funds according to PMK No 190 of 2021.This study aims to determine the Analysis of the Government's Internal Control System in the Management of Village Funds in Cibatok II Village, Cibungbulang District, Bogor Regency. The research method used in this study is a qualitative approach using descriptive methods where the results of research data are in the form of information collected through observation, interviews and documentation that is reviewed. This research uses primary data obtained directly from the main source. This data collection uses a question and answer process with village officials, namely the Village Head, Village Secretary and Village Treasurer. The data that has been collected will be processed and then analyzed to answer what is in the formulation of this research problem.Based on the analysis that has been carried out in this study, the theory and practice implemented in managing village funds have not fully implemented internal control in managing village funds according to PMK Number 190 of 2021 because there is still an uneven distribution of village funds in the Direct Cash Assistance program to the poor so that The Village Government must further improve the performance or data collection of its residents.Keywords: village funds. government internal control system, management of village funds according to PMK No 190 of 2021.